Cytometrycal investigation of developing gametophytes on cereals and their hybrids (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The volumes of cells, nuclei and nucleoli as well аs nucleus – cytoplasm and nucleus – nucleolus ratio in developing male and female gametophytes from species and forms in the genera Triticum L., Secale L. and Triticosecale Wittmark as well as F1 T. aestivum x S. cereale were determined. The changers of there indices during development gametophytes were regular. Some crises periods in development gametophytes as well as signs of normal or pathological course of gametogenesis of cereals have been determined. The hypothesis on connection between degree of the chromatin condensation and quantity of cytoplasm in female gametes been substantiаited.
Keywords: cytometrical characteristics, male and female gametophytes, cereals, wheat-rye hybrid.